Dose–Response Analysis of Locomotor Activity and Stereotypy in Dopamine D3 Receptor Mutant Mice Following Acute Amphetamine - McNAMARA, ROBERT K. (2006)
Accumulating evidence suggests that dopamine D3 receptor (D3R) stimulation is inhibitory to spontaneous and psychostimulant-induced locomotion through opposition of concurrent D1R and D2R-mediated signaling. To evaluate this model, we used homozygous D3R mutant mice and wild-type controls to investigate the role of the D3R in locomotor activity and stereotypy stimulated by acute amphetamine (AMPH) (0.2, 2.5, 5.0, 10.0 mg/kg). At the lowest dose tested (0.2 mg/kg), neither D3R mutant mice nor wild-type mice exhibited measurable change in locomotor activity or stereotypy relative to their respective saline-treated controls. D3R mutant mice exhibited a significantly greater increase in locomotor activity, but not stereotypy, relative to wild-type mice in response to treatment with AMPH 2.5 mg/kg. AMPH-induced locomotor activity and stereotypy were similar in both wild-type and D3R mutant mice at both the 5.0 and 10 mg/kg AMPH doses. These findings provide further support for an inhibitory role for the D3R in AMPH-induced locomotor activity, and demonstrate a more limited role for the D3R in modulating AMPH-induced stereotypy.